Human Resource Management and its Impact on the Level of Job Performance: An Analytical Research in the Iraqi Ministry of Interior - Mamdooh, Salah Naser; Salman, Saadoon Muhsin (Journal of Economics and Administrative Sciences, 2021)
The current research aims to highlight the role of human resource management with its practices (human resource planning, selection and placement, training and development, performance evaluation, compensation, and incentives) in raising the level of individuals' performance and its dimensions (task performance, contextual performance, unproductive work behavior, and adaptive performance) by explaining the research problem, which can be limited to the low level of performance of individuals, where the researchers use the descriptive analytical approach and the SPSS program in the practical aspect of the research community represented by the general manager and his assistant and directors of directorates, departments and divisions in the General Directorate of Human Resources Management, amounting to 180 individuals, where a sample of 130 individuals was selected. The researchers use the questionnaire and the method of personal interviews for collecting data from the research community. The most prominent statistical methods were used (ratios and frequencies, the arithmetic mean, standard deviation, and confirmatory and exploratory factor analysis). The researchers reached a set of recommendations, the most prominent of which was to continue to adopt work force dependent on university qualifications with accreditation holders of higher university degrees in the specialization of management and human resources and the most important result is that most of the managers are of the male gender and have both higher and primary university qualifications. It is presented at the end of the research